SARC025 arms 1 and 2: A phase 1 study of the poly(ADP‐ribose) polymerase inhibitor niraparib with temozolomide or irinotecan in patients with advanced Ewing sarcoma. Issue 8 (8th December 2020) - Chugh, Rashmi; Ballman, Karla V.; Helman, Lee J.; Patel, Shreyaskumar; Whelan, Jeremy S.; Widemann, Brigitte; Lu, Yao; Hawkins, Douglas S.; Mascarenhas, Leo; Glod, John W.; Ji, Jiuping; Zhang, Yiping; et al.
Abstract : Background: In preclinical Ewing sarcoma (ES) models, poly(adenosine diphosphate ribose) polymerase (PARP) inhibitors were identified as a potential therapeutic strategy with synergy in combination with cytotoxic agents. This study evaluated the safety and dosing of the PARP1/2 inhibitor niraparib (NIR) with temozolomide (TMZ; arm 1) or irinotecan (IRN; arm 2) in patients with pretreated ES. Methods: Eligible patients in arm 1 received continuous NIR daily and escalating TMZ (days 2‐6 [D2‐6]) in cohort A. Subsequent patients received intermittent NIR dosing (cohort B), with TMZ re‐escalation in cohort C. In arm 2, patients were assigned to NIR (days 1‐7 [D1‐7]) and escalating doses of IRN (D2‐6). Results: From July 2014 to May 2018, 29 eligible patients (23 males and 6 females) were enrolled in arms 1 and 2, which had 7 dose levels combined. Five patients experienced at least 1 dose‐limiting toxicity (DLT) in arm 1 (grade 4 [G4] neutropenia for >7 days or G4 thrombocytopenia), and 3 patients experienced at least 1 DLT in arm 2 (grade 3 [G3] colitis, G3 anorexia, or G3 alanine aminotransferase elevation). The maximum tolerated dose was NIR at 200 mg every day on D1‐7 plus TMZ at 30 mg/m 2 every day on D2‐6 (arm 1) or NIR at 100 mg every day on D1‐7 plus IRN at 20 mg/m 2 every day on D2‐6 (arm 2). One confirmed partial response was observed in arm 2; the median progression‐free survival was 9.0 weeks (95% CI, 7.0‐10.1 weeks) and 16.3 weeks (95% CI, 5.1‐69.7 weeks) in arms 1 and 2, respectively. The median decrease in tumor poly(ADP‐ribose) activity was 89% (range, 83%‐98%). Conclusions: The combination of NIR and TMZ or IRN was tolerable, but at lower doses in comparison with conventional cytotoxic combinations. A triple‐combination study of NIR, IRN, and TMZ has commenced. Abstract : Preclinical evaluations have identified the EWS‐FLI1 translocation, pathognomonic of Ewing sarcoma, as a predictive factor of response to poly(adenosine diphosphate ribose) polymerase (PARP) inhibitors with synergistic cell death in vivo with DNA damaging agents. This phase 1 study examines the dosing and safety of a combination of the PARP inhibitor niraparib with temozolomide or irinotecan.